2020
DOI: 10.1111/dth.14438
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of low‐dose isotretinoin for treatment of acne vulgaris: Focus on indication, dosage, regimen, efficacy, safety, satisfaction, and follow up, based on clinical studies

Abstract: Oral isotretinoin is the most effective treatment for moderate to severe acne and its side effects are mostly dose‐dependent. Low dose isotretinoin (0.5 mg/kg/day for 1 week every 4 weeks for 6‐months) could be effective and even in its end result, comparable with high or optimal doses. In this systematic review, we aimed to sum up the results of clinical trials regarding indications, dosage, prescription protocol, effectiveness, side effects, patient satisfaction, recurrence rate, and follow‐up period of low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
1
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 32 publications
(98 reference statements)
0
35
1
11
Order By: Relevance
“…7 Moreover, we have studied the effects of various factors on the treatment of acne vulgaris and related scars and its complications. 5,7,[9][10][11][12][13][14][15] In the present The limited use of trichloroacetic acid on ICE-PICK scars, known as the chemical reconstruction of skin scars (CROSS), was first described by Lee et al 16 They reported better results after the use of 100% TCA compared to 65% TCA, because in the TCA 65% group there was an excellent improvement in scars after six sessions and in the TCA 100% group after three sessions. 16 Brodland et al showed that the use of TCA in high concentrations causes protein precipitation, coagulation necrosis of epidermal cells, and collagen necrosis of papillary and reticular dermis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Moreover, we have studied the effects of various factors on the treatment of acne vulgaris and related scars and its complications. 5,7,[9][10][11][12][13][14][15] In the present The limited use of trichloroacetic acid on ICE-PICK scars, known as the chemical reconstruction of skin scars (CROSS), was first described by Lee et al 16 They reported better results after the use of 100% TCA compared to 65% TCA, because in the TCA 65% group there was an excellent improvement in scars after six sessions and in the TCA 100% group after three sessions. 16 Brodland et al showed that the use of TCA in high concentrations causes protein precipitation, coagulation necrosis of epidermal cells, and collagen necrosis of papillary and reticular dermis.…”
Section: Discussionmentioning
confidence: 99%
“…Since the use of timolol in accelerating wound healing has received less attention, we, in a review article, reviewed the studies on this topic 7 . Moreover, we have studied the effects of various factors on the treatment of acne vulgaris and related scars and its complications 5,7,9–15 . In the present study, for the first time in a randomized clinical trial, the interaction of TCA‐CROSS, topical timolol, and saline injection in the treatment of atrophic acne scars were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have been conducted regarding its efficacy and relapse rate after 4-6 months of treatment with low to high dosages of oral isotretinoin. Systematic reviews and meta-analysis of a large number of studies show that the success rate with this drug ranges from 85% to 90% in reducing resistant acne and preventing its recurrence in the long term [7]. However, this drug hosts a wide range of side effects, a rare one being new-onset myopia.…”
Section: Discussionmentioning
confidence: 99%
“…These pathways also lead to the EMT status by applying Snail and Slug transcription factors, and increasing the expression of E-Cadherin and N-cadherin molecules; by inducing this process in cells, they lead to resistance to chemotherapy in people with malignancy [ 19 ]. Studies show an increase in IL-6 levels in cancer patients with COVID-19, indicating a cytokine storm [ 20 , 21 ]. It is hypothesized that, due to cytokine storms, elevated IL-6 levels in COVID-19 cancer patients and using the mentioned pathways in them, the phenomenon of resistance to chemotherapy drug occurs; it is accompanied by therapeutic effect decrement, increased mortality and survival reduction in patients.…”
Section: Il-6mentioning
confidence: 99%